Analysis of the development of symbolic thinking abilities of children aged 5-6 years at Immanuel Kindergarten, Samarinda - Reni Ardiana; Helenita; Ika Apriati (Institute of Accounting Research and Novation (IARN), 2023)
The purpose of this study was to determine the development of symbolic thinking skills in children aged 5-6 years at Kindergarten Immanuel Samarinda. This research uses a qualitative descriptive research type. Data collection techniques used in research are observation, documentation and interviews. The data analysis used in this study is the qualitative data analysis belonging to Miles and Huberman. The process of playing while learning activities such as counting the number of friends before entering class, writing the date before starting the activity, singing while clapping.